MAPPING POTENTIAL VILLAGES TOWARDS AGRICULTURE-BASED TOURISM VILLAGE IN KUMPULREJO, ARGOMULYO SALATIGA DISTRICT - Samtono Samtono; Krisnawati Setyaningrum Nugraheni Krisnawati Setyaningrum Nugraheni; Nina Mistriani; Tri Maryani (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
The mapping of tourism potential in the village of kumpulrejo is important for the development of pioneering tourism villages. The tourist attraction of Kumpulrejo village as a tourist destination is tani rukun santosa group and coffee plantation. The pioneering development of the kumpulrejo tourism village requires creative efforts to create and issue a unique character. Kumpulrejo Village is one of the pioneering tourism villages in the city of Salatiga, Argomulyo district. The community service activity is a collaboration of the STIEPARI Semarang service team with the Salatiga city government to support the tourism development program of the city of Salatiga as a gastronomy city. The purpose of this service is to map the tourism potential of the kumpulrejo village and map the strategies that need to be done to become an agriculture-based tourism village. With the mapping of the tourism potential of Kumpulrejo village, it is hoped that this roadmap will be the first step in developing the Kumpulrejo tourist village.